Bidirectional infrasonic ducts associated with sudden stratospheric warming events. Issue 3 (5th February 2014) - Assink, J. D.; Waxler, R.; Smets, P.; Evers, L. G.
<x xml:space="preserve">Abstract</x> In January 2011, the state of the polar vortex in the midlatitudes changed significantly due to a minor sudden stratospheric warming event. As a result, a bidirectional duct for infrasound propagation developed in the middle atmosphere that persisted for 2 weeks. The ducts were due to two zonal wind jets, one between 30 and 50 km and the other around 70 km altitude. In this paper, using microbarom source modeling, a previously unidentified source region in the eastern Mediterranean is identified, besides the more well known microbarom source regions in the Atlantic Ocean. Infrasound data are then presented in which the above mentioned bidirectional duct is observed in microbarom signals recorded at the International Monitoring System station I48TN in Tunisia, from the Mediterranean region to the east and from the Atlantic Ocean to the west. While the frequency bands of the two sources overlap, the Mediterranean signal is coherent up to about 0.6 Hz. This observation is consistent with the microbarom source modeling; the discrepancy in the frequency band is related to differences in the ocean wave spectra for the two basins considered. This work demonstrates the sensitivity of infrasound to stratospheric dynamics and illustrates that the classic paradigm of a unidirectional stratospheric duct for infrasound propagation can be broken during a sudden stratospheric warming event.